CHARACTERISTICS OF THE COURSE OF LEUCOCYTOCLASTIC VASCULITIS WITH SKIN LESIONS. ANALYSIS OF CLINICAL CASES - O.A. Borzykh; O.V. Belan; I.A. Mormol; Y.M. Avramenko; T. Іengalychev; T.M. Markina (Проблеми екології та медицини)
The article describes the features of the course of leukocytoclastic skin vasculitis with consideration of 3 clinical cases. Leukocytoclastic vasculitis of the skin (LCV) is an isolated cutaneous vasculitis without damage to internal organs. At present, vasculitis is considered a polyetiological disease. The most frequent causes of the development of vasculitis limited to the skin include various acute or chronic infections: bacterial, viral, and fungal. It can be caused by medications, and sometimes the cause cannot be found. When LVC is suspected, an extensive examination is usually required to determine whether the process is limited to the skin or is a manifestation of systemic vasculitis or other systemic diseases. Diagnosis and treatment of LCV is a complex problem in the practice of doctors of many specialties, such as rheumatologists, dermatologists, and therapists, family doctors, which requires close cooperation of specialists. We present 3 clinical cases of patients who were hospitalized in the clinic with symptoms of skin lesions and suspicion of LCV after taking medications. The paper describes various skin manifestations and the results of the examination and treatment. The differential diagnostics enabled us to diagnose LCV in 2 cases, in one case – generalized urticaria due to taking furazolidone. It should be noted that drug reactions with skin lesions constitute a serious medical problem, whose relevance is increasing every year. This is largely due to widespread uncontrolled drug intake among the population, and frequent polypharmacy during treatment under the supervision of medical professionals. Multidisciplinary problems, which are solved by doctors of various specialties at different stages and levels of medical care, including drug-induced skin lesions in patients, are particularly difficult. Strengthening medical control over the prescription and administration of medicinal products, and improving the awareness of doctors of all specialties regarding the diagnosis and treatment of medicinal reactions is the way to solve the problem.